ANALISIS PERKEMBANGAN PENERAPAN BUILDING INFORMATION MODELING (BIM) PADA PROYEK APARTEMEN DI INDONESIA - SARIFAH, FITRIANA (Jurnal Ilmiah Poli Rekayasa, 2024)
The application of Building Information Modeling (BIM) in Indonesian construction has also been carried out in apartment projects. BIM is a process of managing construction during the life cycle of apartment buildings, from planning, design, construction, and use to maintenance. The process The scope of this research is an apartment project built by 3 (three) BUMN construction, namely PT PP (Persero) Tbk (PTPP), PT Wijaya Karya (Persero) Tbk (WIKA), and PT Adhi Karya (Persero) Tbk (ADHI). This study aims to analyze the development of BIM implementation in apartment projects built by the three BUMN contractors. The apartments in this study are apartments with the application of BIM that have been used, not apartments still being built. This research method is carried out with a secondary data content analysis approach, especially the company's annual report that can be accessed by the public from the company's official website, including the identification of apartment projects that have been built and apply BIM to analyze the application of BIM in apartment projects. The results of this study are apartments that have been completed with the application of BIM by PTPP since 2017, ADHI since 2018, and WIKA since 2019. The number of apartments that have been completed with the application of BIM in this study are 4 apartments by WIKA, 5 apartments by PTPP, and 7 apartments by ADHI. All apartments that have been completed with the application of BIM in this study are located on the island of Java.